Analysis of Intention to Use E-Wallet Dana with the Utaut Approach and Perceived Risk - Taibah, Zuryatan Taibah; Rahmayanti, Dewi Rahmayanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The use of digital wallet applications will continue to grow in Indonesia. This research intends to see how the Unified Theory Of Acceptance And Use Of Technology (UTAUT) model introduced by (Vankatesh, 2003) and perceived risk in influencing a person's intention to use a digital wallet. The research data was collected by distributing questionnaires online through G- form. A total of 110 samples were used in this study. Data processing was carried out using smartpls. From the results of the study, it was found that the variables of performance expectancy, effort expectancy, social influence, and facilitating conditions have a positive and significant effect on the intention to use the DANA e-wallet, while the perceived risk variable has no influence on the intention to use the DANA e-wallet.